ANALISIS KESIAPAN SARANA DAN PRASANA ASESMEN NASIONAL BERBASIS KOMPUTER DI SMK NEGERI KABUPATEN KOTAWARINGIN TIMUR - Muzakki Muzakki; Abdul Gofur; Rio Irawan; Slamet Riyadi; Matkholil Matkholil (Mudir : Jurnal Manajemen Pendidikan, 2022)
This study aims to explore the readiness of facilities and infrastructure for the implementation of the Computer-Based National Assessment (ANBK) which was conducted at Sampit 1 SMKN, Kotawaringin Timur 1 SMKN and SMKN 1 Cempaga, East Kotawaringin Regency as schools participating in the National Assessment. The research method uses descriptive qualitative research. The research subjects in this study were school principals, vice principals and proctors and technicians. The research results obtained in the field included the implementation of ANBK at Sampit 1 Vocational High School, Besi Kota 1 Vocational School and Cempaga 1 Public Vocational School which was carried out online, equipped with complete computers, laptops, tablets, as well as the availability of a computer lab and the availability of qualified proctors and technicians. Obstacles encountered include unstable internet network, disruption of the central server to sudden power outages which result in disruption of ANBK implementation.